ANALISIS PENGENDALIAN WAKTU PADA PROYEK PEMBANGUNAN JALAN FLEXIBLE PAVEMENT KOLEKTOR (JL. WIYUNG – LIDAH WETAN) DENGAN MENGGUNAKAN METODE EARNED VALUE MANAGEMENT SYSTEM - Lubabul Hikam, Mochammad Chaidar; Fauzi Rizky Riza Wardana; Achmad Dzulfiqar Alfiansyah (Kohesi: Jurnal Sains dan Teknologi, 2024)
The construction of road infrastructure plays a crucial role in enhancing connectivity and driving economic growth, including in Surabaya City, East Java. This study analyzes the Flexible Pavement Collector Road construction project on Jl. Wiyung – Lidah Wetan using the Earned Value Management System (EVMS) method to evaluate project performance and identify acceleration strategies. Primary data, including the time schedule, budget plan, and weekly progress reports, were used to calculate BCWS, BCWP, SV, SPI, ETC, and EAC values. The analysis results indicate that the project experienced significant delays, with a progress deviation of up to -28.57% in the 22nd week. The average SPI value of 0.63 (<1) indicates low resource utilization efficiency. The main factors causing the delays include incomplete land acquisition, slow utility relocation, labor shortages, and adverse weather conditions. Acceleration efforts were focused on critical paths covering work items with a volume weight of 80%, using Network Planning Diagrams to prioritize activities. Calculations showed that the project could be accelerated by an additional 11 days; however, it still experienced a 4-day delay from the initial schedule. To address this, the remaining work was completed during the maintenance phase by adding resources.This study underscores the importance of integrated project management aligned with SDG principles to support sustainable infrastructure development.